Barriers in precision medicine implementation among Advanced Nonsquamous Cell Lung Cancer-patients: A Real-World Evidence Scenario - Flavia A. Duarte; Carlos Gil Ferreira; Rodrigo Dienstmann; Bruno L. Ferrari; Matheus Costa E Silva; Pedro Nazareth A. Junior; Paulo Guilherme de O. Salles; Paulo Henrique C. Diniz (Journal of Market Access & Health Policy)
Background Precision oncology has a prominent role in nonsquamous non-small cell lung cancer (nsNSCLC) treatment progress; however, its access in a real-world scenario might be limited.Objective To investigate the time spent in nsNSCLC molecular profile evaluation and its influence on clinical decisions.Methods nsNSCLC patients who underwent molecular testing in a private referral Brazilian center between November 2015 and February 2020 were identified. The interval from nsNSCLC diagnosis to the characterization of the molecular profile was determined. Other outcomes, focusing on the biomarker tissue journey, were also assessed.Results In this cohort (n = 78), the median time between the advanced nsNSCLC diagnosis and biomarker characterization was 40.5 days (range, 29.5–68.5). The median interval between the diagnosis and the test request was longer than the interval between the request and the results (respectively 29.0 versus 12.0 days; p < 0.001). At the treatment initiation, 51% (36/71) of the patients who received any systemic therapy did not have their driver mutations panel results available. But on these, 42% (15/36) had a targetable alteration identified later on. Among patients harboring a targetable alteration, only 46% (n = 13/28) received a tyrosine kinase inhibitor (TKI) as first-line therapy. The median time to the TKI initiation was even longer than the median time to all treatment initiation (92.0 versus 40.0 days).Conclusions Our data show a long median time from advanced nsNSCLC diagnosis and the availability of the biomarker testing in medical practice, which impacted the choice of a non-personalized therapy as the first-line.